Shock insulation groove waterproof measure - JIN YANDONG (2023)
The invention provides a waterproof measure for a shock insulation groove. The waterproof measure comprises a building ground, a foundation pier, the shock insulation groove and an additional waterproof layer. The shock isolation groove is formed in the periphery of the foundation pier and used for being isolated from the building ground; one end of the additional waterproof layer is fixedly arranged at the bottom of the building ground, and the other end of the additional waterproof layer is fixedly arranged in the side wall of the foundation pier through the bottom of the seismic isolation groove and used for waterproofing of the bottom of the seismic isolation groove; the outer side of one end, arranged in the side wall of the foundation pier, of the additional waterproof layer is coated with a water swelling material, and the water swelling material is used for generating swelling when water exists to increase the pressure between the additional waterproof layer and the concrete. The additional waterproof